Pediatric rheumatology a color handbook - Reed, Ann Marie; Mason, Thomas G. (Color handbook., 2012)
Fully illustrated in colour, this book aims to help clinicians assess children with potential rheumatic disease. The most frequently recognised symptom complexes in children are emphasised, with initial focus on musculokeletal diseases that may have multi-organ involvement, then more specific conditions are discussed.